ClBRN1 from Chrysanthemum lavandulifolium enhances the stress resistance of transgenic Arabidopsis - Li,Yanxi; He,Wenting; Liu,Yueyue; Mei,Chendi; Wang,Hai; Song,Xuebin (PeerJ, 2024)
Background Chrysanthemum (Chrysanthemum×morifolium Ramat.) is a particularly important autumn perennial flower for potted plant, flower bed and border, and cut flower with high ornamental value. However, abiotic stress can affect the ornamental quality of Chrysanthemum. NAC (NAM, ATAF1-2, and CUC2) transcription factors (TFs) play an important role in regulating plant growth and development, as well as responding to abiotic stresses. Methods In this study, the ClBRN1 (Chrysanthemum lavandulifolium BEARSKIN gene) was isolated from the Chrysanthemum model plant C. lavandulifolium. And analyze the function of the gene through bioinformatics, subcellular localization and overexpression. Results Bioinformatics analysis showed that the ClBRN1 gene was a member of the NAC TFs family, with a CDS (coding sequence) length of 1,080 bp and encoding 359 amino acids. The subcellular localization results found that the gene was located in the nucleus and cell membrane. Furthermore, the transgenic results in Arabidopsis thaliana showed that the gene significantly reduces plant height while improving salt and low temperature tolerance. Observation of paraffin sections of Arabidopsis stems also revealed that the secondary cell wall of overexpressing Arabidopsis stems was significantly thicker than that of wild-type. The above results indicate that the ClBRN1 gene may play an important role in regulating plant resistance to abiotic stress. This study will provide new insights for molecular breeding of resistant chrysanthemums in the future.
Keywords: Chrysanthemum lavandulifolium; ClBRN1; Stress resistance; Functional verification